Development of enhanced air-cooled heat sink arrays - Ku, Kevin Sheng Wen (Nanyang Technological University, 2020)
This project presents the forced convective heat transfer performances of tree-shaped heat sinks fabricated by Selective Laser Melting (SLM). Tree-shaped heat sinks were designed using methods of Constructal Theory and were investigated using simulations to develop an improved tree-shaped heat sink design in terms of heat transfer performance. Tree-shaped heat sinks with bifurcation angles ranging from 90° to 109.47° were fabricated and investigated experimentally and numerically. The experimental and numerical results were compared and the effects of bifurcation angles on heat transfer performance were examined. Experiments were conducted in a vertical duct flow channel with Reynolds number (Re) ranging from 2970 to 20979. The heat transfer coefficient (h) and the Nusselt number (Nu) were computed based on the base area of the heat sink (Ab). The results for the experiments showed that the 90° heat sink specimens had a maximum of 6.0 % and 6.5 % enhancement in h than the 100˚ and 109.47˚ bifurcation heat sink specimens, respectively. The simulation results showed a similar trend with 90° heat sink specimen having a maximum of 7.4 % and 7.5 % enhancements in h than the 100˚ and 109.47˚ heat sink specimens, respectively. The Nusellt number of experimental and simulation results showed a similar trend with the 90° heat sink specimen having the best performance among the heat sinks.